2023
DOI: 10.1136/heartjnl-2022-321609
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial phasic function: physiology, clinical assessment and prognostic value

Abstract: Left atrial (LA) phasic function provides significant insights into the pathophysiology of cardiovascular disease. LA function is described in three phases: reservoir (atrial filling, during systole), conduit (passive emptying, during early diastole) and contractile (active emptying, during late diastole). LA phasic function can be evaluated by different imaging modalities, and a variety of techniques including volumetric analysis, deformation (strain) and Doppler methods. LA phasic function (particularly LA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
0
16
0
3
Order By: Relevance
“…It is increasingly recognized that "atrial cardiopathy" is a contributing pathogenic construct associated with ESUS. 1,2 This model fits into the concept of the heart-brain axis which recapitulates all the circuits that regulate communication between heart and brain. 3 Optimal bidirectional communication between the heart and the brain warrants homeostasis, but may also entail (coupled) pathological deviations if one of the two systems is disturbed.…”
Section: Introductionmentioning
confidence: 83%
“…It is increasingly recognized that "atrial cardiopathy" is a contributing pathogenic construct associated with ESUS. 1,2 This model fits into the concept of the heart-brain axis which recapitulates all the circuits that regulate communication between heart and brain. 3 Optimal bidirectional communication between the heart and the brain warrants homeostasis, but may also entail (coupled) pathological deviations if one of the two systems is disturbed.…”
Section: Introductionmentioning
confidence: 83%
“…Atrial fibrillation (AF) generation and perpetuation are associated with functional and structural atrial changes, which lead to dilatation and interstitial fibrosis as an arrhythmogenic substrate 20 . Impaired LA functions have been shown to predict AF incidents 21 . LAA is more compliant and therefore plays an important role in the LA reservoir function by modifying LA pressure‐volume relationships.…”
Section: Discussionmentioning
confidence: 99%
“…20 Impaired LA functions have been shown to predict AF incidents. 21 LAA is more compliant and therefore plays an important role in the LA reservoir function by modifying LA pressure-volume relationships. Therefore, LAA flow velocity was believed to be a reliable indicator of contractile and reservoir function in the LA.…”
Section: The Possible Mechanisms Association Between Laa Flow Velocit...mentioning
confidence: 99%
“…Recent studies have highlighted the value of alternative echocardiographic measures such as left atrial strain and minimal left atrial volume, with both measures shown to have better correlation with left ventricular filling pressure and/or outcomes compared with the current approach of using maximal left atrial volume. [24][25][26] Beyond natriuretic peptides, novel biomarkers such as galectin-3 have Perspectives also shown promise in HFpEF diagnosis and risk stratification. 27 There is also emerging awareness of different HFpEF phenotypes, which could partly explain the failure of previous treatment efficacy studies that have taken a "one-size-fits-all" approach to management.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent studies have highlighted the value of alternative echocardiographic measures such as left atrial strain and minimal left atrial volume, with both measures shown to have better correlation with left ventricular filling pressure and/or outcomes compared with the current approach of using maximal left atrial volume 24‐26 . Beyond natriuretic peptides, novel biomarkers such as galectin‐3 have also shown promise in refining HFpEF diagnosis and risk stratification 27 .…”
Section: Future Directionsmentioning
confidence: 99%